Clinicopathological relevance of granular C4d deposition in peritubular capillaries of kidney allografts. (16th January 2014) - Kikić, Željko; Kozakowski, Nicolas; Regele, Heinz; Priessner, Karin; Nordmeyer, Veit; Marinova, Lena; Zlabinger, Gerhard J.; Wahrmann, Markus; Bartel, Gregor; Böhmig, Georg A.
Summary While linear C4d staining in peritubular capillaries (PTC) is established as a marker of antibody‐mediated rejection, the significance of a distinct granular C4d deposition pattern has not yet been clarified. In this study, 329 renal allograft recipients who underwent indication biopsies were analysed for immunohistochemical C4d staining characteristics. Fifty‐six (17%) recipients showed granular C4d in PTC, without any relationship to conventional risk factors and morphological features of rejection. We found a strong association with long‐term overall graft survival (7‐year survival: 41% vs. 66% in granular C4d‐negative subjects, P = 0.001), which was mainly driven by a greater risk of mortality [hazard ratio: 3.12 (95% confidence interval: 1.23–7.94); P = 0.02]. Granular C4d was associated with delayed graft function [39% vs. 22% (C4d‐negative subjects), P = 0.007], higher 1‐year serum creatinine [median 2.1 (interquartile range: 1.7–2.6) mg/dl vs. 1.6 (1.3–2.0) mg/dl, P = 0.001] and a trend towards worse death‐censored graft survival (P = 0.07). In support of a role of capillary immune complex formation, granular C4d was associated with electron‐dense deposits in PTC basement membranes, which were occasionally accompanied by focally distributed capillary IgG deposits. In conclusion, our study suggests clinical relevance of detecting capillary granular C4d deposition. Our results point to a pathogenetic role of alloimmune‐independent immune complex deposition.